Effects of valproic acid and pioglitazone on cell cycle progression and proliferation of T-cell acute lymphoblastic leukemia Jurkat cells - Marie Saghaeian Jazi; Saeed Mohammadi; Yaghoub Yazdani; Sima Sedighi; Ali Memarian; Mehrdad Aghaei (Iranian Journal of Basic Medical Sciences, 2016)
Objective(s): T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematologic malignant tumor. Administration of chemical compounds influencing apoptosis and T cell development has been discussed as promising novel therapeutic strategies. Valproic acid (VPA) as a recently emerged anti-neoplastic histone deacetylase (HDAC) inhibitor and pioglitazone (PGZ) as a high-affinity peroxisome proliferator-activated receptor-gamma (PPARγ) agonist have been shown to induce apoptosis and cell cycle arrest in different studies. Here, we aimed to investigate the underlying molecular mechanisms involved in anti-proliferative effects of these compounds on human Jurkat cells. Materials and Methods: Treated cells were evaluated for cell cycle progression and apoptosis using flowcytometry and MTT viability assay. Real-time RT-PCR was carried out to measure the alterations in key genes associated with cell death and cell cycle arrest. Results: Our findings illustrated that both VPA and PGZ can inhibit Jurkat E6.1 cells in vitro after   24 hr; however, PGZ 400 μM presents the most anti-proliferative effect. Interestingly, treated cells have been arrested in G2/M with deregulated cell division cycle 25A (Cdc25A) phosphatase and cyclin-dependent kinase inhibitor 1B (CDKN1B or p27) expression. Expression of cyclin D1 gene was inhibited when DNA synthesis entry was declined. Cell cycle deregulation in PGZ and VPA-exposed cells generated an increase in the proportion of aneuploid cell population, which has not reported before. Conclusion: These findings define that anti-proliferative effects of PGZ and VPA on Jurkat cell line are mediated by cell cycle deregulation. Thus, we suggest PGZ and VPA may relieve potential therapeutic application against apoptosis-resistant malignancies.